The Influence of Service Quality, Distribution Channels, and Promotion on Sales Volume at PT Delta Agro Makmur Medan - Rosinta Romauli Situmeang; Antoni Antoni; Jesinda Patricia; Devin Reinaldo (Institute of Computer Science (IOCS), 2020)
This research was conducted at PT. Delta Agro Makmur Medan. The purpose of this study was to test and analyze the influence of Service Quality, Distribution Channels and Promotion on Sales at PT Delta Agro Makmur Medan. The population in this study amounted to 139 cases and a sample of 94. The results showed that partially Service Quality has a positive and significant effect simultaneously on Sales Volume. Partially Distribution Channels have a positive and significant effect simultaneously on Sales Volume. Partially Promotion has a positive and significant effect simultaneously on Sales Volume. Simultaneously, Service Quality, Distribution Channels, and Promotion have a positive and significant effect simultaneously on Sales Volume at PT. Delta Agro Makmur Medan.